Optimizing the Role of Bhabinkamtibmas in Preventing the Crime of Theft with Weights at Madiun Police - Udayana, I Made Prema Dharma (Police Studies Review, 2024)
Keyw The crime rate in Indonesia is still high, one of which is the case of aggravated theft, including Madiun Regency with 26 cases in 2022. Therefore, an optimal role of Bhabinkamtibmas is needed to prevent the crime of aggravated theft. This research uses a descriptive qualitative approach with a field research method. This research uses Role Theory, Communication Science Theory, Work Efficiency Theory, and Crime Prevention Theory along with Optimization Concept, Harkamtibmas Concept, Bhabinkamtibmas Concept, and Curat Crime Concept. The results showed that the role of Bhabinkamtibmas in preventing burglary in the Madiun Police jurisdiction was not optimal in accordance with Perkap Nomor 21 Tahun 2007. The influencing factors are the time of task execution, motivation, and completeness of facilities. Social Crime Prevention, Situational Crime Prevention, and Community-Based Crime Prevention strategies have not run optimally according to Perkap Nomor 3 Tahun 2015. Researchers recommend improving the ability of Bhabinkamtibmas to communicate, improving facilities and infrastructure, and increasing the capacity of Bhabinkamtibmas and the variety of activities.